The Post-Authoritarian Chilean Party System between Continuity and Change - Uğur Tekiner (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
This article aims to examine to what extent the post-authoritarian Chilean party system changed in comparison to the period prior to the 1973 coup. Based on an analysis of the period from 1990 until 2010 against the background of the pre-1973 period and the military dictatorship (1973-1990), the main argument of this article is that the post-authoritarian Chilean party system oscillated between continuity and change. Whilst continuity found its roots in the pre-authoritarian period and Chile’s long-running democratic tradition, change was particularly enforced by the anti-democratic practices of the military government. As such, this study has pinpointed three interrelated tensions between continuity and change that characterised the post-authoritarian party system: the centrality of parties vs. the growing public disillusionment with politics; the pro-/anti-authoritarian cleavage vs. the consensus-based relations between parties; and the tripartite party system vs. the bipolar coalition politics. This tension profoundly influenced all the political parties and inter-party coalitions that functioned during this period, not least the ruling Concertación bloc.